The making of business news in Africa: a case study of Cameroon Tribune newspaper - Tawe, Ngamale Emmanuel (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2012)
Since the emergence of business journalism as a genre within the broad spectrum of news reporting, most of the scholarly works into its development have focused on growth in the western (that is developed) world. This indicates that very limited research has been done in the field of business journalism in the developing economies. Thus there exist gaps in understanding the practice of business journalism in Africa and part of this is rooted in how the practice is defined. This study aims to shed light on the practice of business journalism in this African context. It explores the onset and development of business journalism and its evolution in Africa. The main focus in this case study was to understand the definition of business news in the specific context of the Cameroon Tribune. Individual in-depth interviews were used as the main (primary) data collection method along with observation and cursory reading as complementary (secondary) methods. This study is influenced by the sociology of news production which foregrounds theoretical frames such as news construction and gatekeeping. Findings from this study reveal that business news at the Cameroon Tribune is elitist, essentially defined around personality and, is in the most part, development news. Additional findings indicate that the absence of any editorial guidelines leaves most reporters secondguessing how to please management with socialised values mostly acquired through peer learning. In conclusion, this study advances the necessity for the Africanisation of business news. This would entail reporting financial, economic, consumer, and corporate affairs, from a vocabulary and composition context that unveils much exchange taking place in the lives of many Africans.
Keywords: Journalism -- Cameroon; Mass media -- Cameroon; Journalism, Commercial -- Cameroon; Cameroon Tribune (Cameroon); Journalism, Commercial -- Sociological aspects -- Cameroon; Journalism, Commercial -- Social aspects -- Cameroon; Journalism, Commercial -- Economic aspects -- Cameroon; Journalism, Commercial -- Political aspects -- Cameroon; Cameroon -- Economic conditions; Elite (Social sciences)